Improvement proposal to increase productivity of a SME in the primary manufacturing sector using standardized labor and TPM tools - Obregon Leon, Dahana Anthuanet (2023)
The case study is situated in a SME in the primary manufacturing sector and focuses on increasing its productivity using lean manufacturing tools. First, productivity was identified at 15%, while the average for the sector was 25%, causing a negative economic impact of approximately U$301,309 per year. Through the diagnosis, it was found that the main reasons were machine downtime, caused by various factors such as unplanned downtime and maintenance; the second reason was inadequate sorting of raw material, due to the lack of standardized procedures, lack of protocols and disorder in the sorting area. To address these problems, an improvement model was developed based on 5S tools, standardized work and TPM (autonomous and preventive maintenance). To validate the model, a pilot project of 5S tools and standardized work was carried out through an internal audit conducted before implementing the tool and after its application, an increase in 5S compliance from 29% to 84% was evidenced. Likewise, the standardized work pilot reduced the cycle time of the raw material classification activity from 708 to 539 seconds thanks to the implementation of a procedures format that standardized the process and eliminated activities with no added value. Regarding TPM, it was validated using Arena software, achieving a 2% improvement in OEE and therefore a 19.4% increase in productivity.